Administração estratégica em micro e pequenas empresas de TI: o caso da empresa Rubi - Weber, Marcos (Universidade do Vale do Rio dos Sinos, 2010)
The information technology sector in 2006 accounted for 8.3% of Brazilian GDP, demonstrating its importance to national economy (IBGE, 2009). The sector is composed of 96% for micro and small businesses, which arise from technical knowledge of entrepreneurs, but with deficiencies in management (STEFFANUTO, 2004). Those deficiencies lead to the closure of 35.9% before completing five years of activity (SEBRAE 2007). This dissertation aims to identify and describe how the strategic management process occurs in a small company in the sector of Information Technology. It is based on the study of schools of strategy outlined by Mintzberg et al. (2000), and also from the strategy vision as social practice pointed out by Clegg, Carter and Kornberger (2004), Jarzabkowski (2003, 2004, 2005), Whittington (2001, 2004) and Wilson and Jarzabkowski (2002, 2004). To develop the research it was adopted case study method. It was studied a firm classified as small business, inserted in the sector of information technology. The analysis showed that the company adopts an informal strategic management researched centered on the board. One noted that this model of strategic management is especially similar to the model described by Mintzberg et al. (2000) as the entrepreneurial school and based in the vision of the entrepreneur. However, data also indicate the presence of features of other schools of strategy throughout the life cycle of the company studied, such as the School of Design, Positioning and the schools of Learning, Cultural and Cognitive. The strategy is communicated in part to employees from formalization into an annual event, and continuously by the perception through the pattern of organizational behavior. The presence of strategy as social practice at the strategic level (directors) was made evident, analyzing the history and the current strategic management of the company. Also one discussed the strategy in practice at the tactical level, near the middle management, through their guidance, their interactions with customers and suppliers, its decision-making, among other practices related to the daily lives of managers. Finally, the dissertation, based on survey data, presents some gaps for future research on the subject, plus a series of suggestions for the company studied.
Keywords: Administração estratégica; Estratégia como prática; Micro e pequenas empresas; Tecnologia da informação; Strategic management; Strategy as practice; Micro and small enterprises; Information technology; ACCNPQ::Ciências Sociais Aplicadas::Administração